(untitled) (Journal of the College of Basic Education, 2022)
The use of training aids as complementary methods to the training process to reduce training timeAchievement, the importance of research lies in developing a training program based on scientific foundationsThe correct use of training methods and their impact on the completion of the 100-meter freestyle swimmingThe research is the lack of use of these means in the training units, and the research aimed to numbersA training curriculum using a training method (parachute) and identifying the impact of the training curriculumPrepared at the level of achievement 100 free swimming, the researchers concluded that the training methodThe high-intensity interval using training methods led to an improvement in the level of achievement in100m freestyle swimming. The researchers recommend the need to use means of resistance within vocabularyThe training curriculum.